Les Obligations Professionnelles du Promoteur Immobilier Face à L’ouverture Economique - Elhaouari , Nedjoua (Journal of Legal Studies and Researches, 2023)
The real estate promotion activity knew radical reforms due to the economic transformations enshrined by the real estate legislation in the field of urban real estate in general and housing in particular to keep pace with the new strategy considering the real estate promoter an economic agent, so it was necessary to lift the monopoly and open free competition for the private sector.